Broadcast Management Analysis of Smart FM Makassar Radio - Mariesa Giswandhani; Muhammad Adnan S (Green Publisher Indonesia, 2023)
The purpose of this research is to find out the management strategy of Smart FM Makassar radio broadcasting in maintaining its existence. The research method used is qualitative. The primary data source is in the form of observations and interviews with three information, namely the stationary manager, program head (producer) and broadcaster while the secondary data source is in the form of informant documents and literature studies. The results showed that based on the application of Susan Tyler Eastman's theory, the strategy applied by Smart FM Makassar radio was maximized. Some of the strategies implemented are the compatibility strategy for program scheduling, program type, and broadcast implementation; habit formation, which is a habit formation strategy, namely choosing and planning the right program that can form the habit of listening for the audience, presenting events regularly and scheduled to stay true to the program of the audience's choice; control of audience flow to increase the number of listeners and prevent moving to other channels; conservation program resources that aim to protect program resources so that they can be stored and reused if needed at some point; and mass appeal (mass appeal) which is the attraction of the mass attractor and the attractiveness of the media.